Dynamics of Intermittent Delayed Emission in Single CdSe/CdS Quantum Dots - Hinterding, Stijn O. M. (J Phys Chem Lett, 2020)
[Image: see text] Bright and fast fluorescence makes semiconductor nanocrystals, or quantum dots (QDs), appealing for applications ranging from biomedical research to display screens. However, a few percent of their fluorescence intensity is surprisingly slow. Research into this “delayed emission” has been scarce, despite undesired consequences for some applications and potential opportunities for others. Here, we characterize the dynamics of delayed emission exhibited by individual CdSe/CdS core/shell QDs and correlate these with changes in the emission spectrum. The delayed-emission intensity from a single QD fluctuates strongly during an experiment of several minutes and is thus not always “on”, implying that control over delayed emission may be possible. Periods of bright delayed emission correlate with red-shifted emission spectra. This behavior is consistent with exciton polarization by fluctuating electric fields due to diffusing surface charges, which have been known to cause spectral diffusion in QDs. Our findings thus provide a stepping stone for future efforts to control delayed emission.